Inhibition of pSTAT1 by tofacitinib accounts for the early improvement of experimental chronic synovitis - Sandra Pérez-Baos; Paula Gratal; Juan I. Barrasa; Ana Lamuedra; Olga Sánchez-Pernaute; Gabriel Herrero-Beaumont; Raquel Largo (BMC, 2019)
Abstract Background In order to gain insight into the early effects drawn by JAK inhibitors on intra-joint JAK/STAT-dependent signaling, we sought synovial activation of STATs and their end-products, along with their modification with tofacitinib (TOFA), at flare-up in antigen induced arthritis (AIA). New Zealand rabbits were randomly assigned to four groups -healthy controls, AIA, TOFA-treated AIA, or TOFA-treated controls-. AIA was induced with 4 weekly intra-articular ovalbumin injections in sensitized animals. TOFA (10 mg·kg− 1·day− 1) was administered for the last 2 weeks. Animals were euthanized 24 h after the last injection. Results AIA animals showed high-grade synovitis, which was partially improved by TOFA. No effects of the treatment were found on serum C-reactive protein or on the synovial macrophage infiltration at this stage. Synovial MMP-1,-3 and -13 expression levels in treated AIA rabbits were found to drop to those of controls, while a downregulation of IL6, IFNγ and TNF was evident in treated versus untreated AIA rabbits. Concurrently, a reduction in pSTAT1 and SOCS1, but not in pSTAT3, SOCS3 or active NFκB-p65, was noted with TOFA. Conclusions Studying the mechanism of action of immunomodulatory drugs represents a major challenge in vivo, since drug-dependent decreases in inflammation very likely mask direct effects on disease mechanisms. This study design allowed us to prevent any confounding effect resulting from reductions in the overall inflammatory status, hence assessing the true pharmacological actions of TOFA in a very severe synovitis. Our findings point to pSTAT1 and MMPs as early molecular readouts of response to this JAK inhibitor.